Optimal utilization of modern reproductive technologies to maximize the gross margin of milk production - Heikkilä, Anna-Maija; Peippo, Jaana (Elsevier, 2012)
In this study, a linear programming model was developed to maximize the gross margin of milk production by determining the optimal use of different reproductive technologies in a dairy herd. The model has the potential to vary the use of conventional artificial insemination, insemination with X-sorted sperm, and the use of unselected or sex-selected embryo recovery and transfer. Data from Finnish dairy herd recording systems were used to parameterize the model. This paper presents the results of 6 scenarios for a herd size of 60 dairy cows. In the basic scenario, the optimum economic combination for Finnish conditions was to inseminate 10 heifers and 22 cows with unsorted semen, 8 heifers with X-sorted sperm, and to use 20 cows as embryo donors which was the upper constraint for this technique. The embryo donors were inseminated with conventional semen for both embryo production and their subsequent pregnancy. Without restriction on embryo recovery, the optimum combination was to use all heifers as donors of sex-selected embryos and all cows as donors of unselected embryos. It was more profitable to produce female embryos with X-sorted sperm than by sorting embryos. Embryo recipients were not economically justified in any scenario. In practice, the optimal strategy is herd-specific depending on the input costs, output values and the technical success of each reproductive technology in that herd. This single-year linear programming model adequately differentiates between breeding technologies within a herd, but further research is needed to develop dynamic models to consider genetic improvement and herd expansion.
Keywords: Ma; sukupuoli; lypsykarja; maidontuotanto; lineaarinen optimointi; dairy cattle; embryo transfer; selection; optimization methods; linear programming; milk production; sex selection